APPLICATION OF CDIO APPROACH TO MSC AND PHD ENGINEERING PROGRAMS - A. I. Chuchalin; N. V. Daneikina (Высшее образование в России, 2017)
The paper presents two-level lists of intended learning outcomes in the MSc’s programs (FCDI Syllabus v1) and PhD programs (FFCD Syllabus v1) on the analogy with the CDIO Syllabus v2 for graduates of basic engineering education programs based on the analysis of generalized requirements of national and international standards for competences acquired by graduates of Master’s degree programs (MSc-programs) and postgraduate programs (PhDprograms) in the field of engineering, technology and technical sciences, taking into account the expert opinion of specific features and priority directions in innovation and research engineering activity. Standards of MSc educational programs (FCDI Standards) and PhD educational programs (FFCD Standards) are developed with a focus on FCDI Syllabus v1 and FFCD Syllabus v1 on the analogy with the CDIO Standards for the basic engineering education programs. The developed lists of competencies of graduates and standards of MSc and PhD educational programs may be subject to further development and detailing in higher educational institutions.